EFFICIENCY OF RANKED SET SAMPLING IN HORTICULTURAL SURVEYS - Jeelani, M Iqbal; Bouza, Carlos N; Sautto, Jose M (Cadernos do IME - Série Estatística, 2015)
DOI: 10.12957/cadest.2015.19114 Abstract In this paper, we explore the feasibility of using RSS (Ranked Set Sampling) in improving the estimates of the population mean in comparison to SRS (Simple Random Sampling) in Horticultural research. We use an experience developed with a survey of apples in India. The numerical results suggest that RSS procedure results in a substantial reduction of standard errors, and thus provides more efficient estimates than SRS, in the specific Horticultural Survey studied, using the same sample size. Then it is recommended as an easy-to-use accurate method to management of this Horticulture problem. Key-words: Ranked Set Sampling, Simple Random Sampling, Standard Error, Accuracy.